Can breathing gases be analyzed without a mouth mask? Proof-of-concept and concurrent validity of a newly developed design with a mask-less headset - Roossien, C.C.; Krops, L.A.; Wempe, J.B.; Verkerke, G.J.; Reneman, M.F. (Applied ergonomics, 2021)
A portable headset has been developed to analyze breathing gases and establish the energetic workload of physically active workers. This proof-of-concept study aimed to investigate the following: (1) the validity of the headset compared to indirect calorimetry using a mouth mask; (2) the validity of the headset compared to the validity of oxygen consumption (V̇O2) estimated on the basis of heart rate; (3) the influence of wind on validity; and (4) user experiences of the headset. Fifteen subjects performed a submaximal cycling test twice, once with the headset, and once with a mouth mask and heartrate monitor. Concurrent validity of the headset was analyzed using an intraclass correlation coefficient (ICC). Across all phases, a good correlation between the headset and mouth mask was observed for V̇O2, carbon dioxide production (V̇CO2) and exhaled volume (V̇E) (ICC≥0.72). The headset tended to underestimate V̇O2, V̇CO2 and V̇E at low intensities and to overestimate it at higher intensities. The headset was more valid for estimating V̇O2 (ICC = 0.39) than estimates based on heart rate (ICC = 0.11) (n = 7). Wind flow caused an overestimation (md ≥ 18.4 ± 16.9%) and lowered the correlation of V̇O2 between the headset and the mouth mask to a moderate level (ICC = 0.48). The subjects preferred the headset over the mouth mask because it was more comfortable, did not hinder communication and had lower breathing resistance. The headset appears to be useable for monitoring development of the energetic workloads of physically active workers, being more valid than heart rate monitoring and more practical than indirect calorimetry with a mouth mask. Proof-of-concept was confirmed. Another design step and further validation studies are needed before implementation in the workplace. •This proof-of-concept study confirms the feasibility of the newly developed headset.•The headset is comfortable, lowers breathing resistance and does not hinder communication.•The ultimate validity and usability of the headset will be positioned between that of the mouth mask and heartrate monitoring.•The fully developed headset will potentially be useable for monitoring the energetic workload of physically active workers.